Sturdy Data Warehouse for Complex Data of Travel Survey (International Journal of Innovative Research in Computer Science & Technology, 2022)
The data warehouse enables information  to be organized in order to ease data handling from one  sphere to the other and to promote knowledge acquisition.  The requirement for a consistent organization and  compatibility across various data sources grows as the  quantity of data grows, making it more difficult to  conduct thorough analyses within short periods. This  study offers a trip data warehouse that uses dimensional  modeling to promote a more comprehensible structure,  comparable findings, quicker data access, and faster  publishing of summaries. The use of multivariate  representation to transport information helps to improve  construction while also integrating, augmenting, and  improving data. It performs data processing and  validation in an automated manner. The development of  transportation planning tools is anticipated to lead to the  creation of a multivariate representation for trip data. In  future, there is a pragmatic scope of extensive research in  this field.
Keywords: Data Warehouse; Data warehouse; Knowledge management; Metadata; Travel survey